2017
DOI: 10.1183/16000617.0056-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in systemic sclerosis: different phenotypes

Abstract: @ERSpublicationsPulmonary hypertension in systemic sclerosis is heterogeneous with various possible mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
98
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 39 publications
2
98
0
5
Order By: Relevance
“…In clinical practice, it may be challenging to classify patients with SSc in a discrete PH group because of complex and frequently overlapping clinical features. Indeed, in the setting of pre-capillary PH, SSc patients may present with no, limited, or extensive ILD and a wide range of hemodynamic severity [ 9 11 ]. However, classification of these patients remains meaningful, as medical therapies are dependent on it.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, it may be challenging to classify patients with SSc in a discrete PH group because of complex and frequently overlapping clinical features. Indeed, in the setting of pre-capillary PH, SSc patients may present with no, limited, or extensive ILD and a wide range of hemodynamic severity [ 9 11 ]. However, classification of these patients remains meaningful, as medical therapies are dependent on it.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that PH associated with the extensive form of SSc-ILD (>20% fibrosis on HRCT or forced vital capacity (FVC) <70% in indeterminate HRCT) could be classified as group 3. 15 Although the etiology of PH is associated with extent of lung disease, the mPAP does not seem to correlate with extent of fibrosis on imaging or the forced vital capacity. 22,24 In patients with SSc-ILD, a diffusion capacity (DLCO) <40% of predicted or a reduction in DLCO out of proportion to FVC (FVC/ DLCO ratio >1.6) also suggests the presence of pulmonary vascular disease.…”
Section: Types Of Pulmonary Hypertension In Systemic Sclerosismentioning
confidence: 98%
“…Due to the systemic nature of SSc, an overlap between more than one type of PH is common (Table 1 and Figure 1), making the identification of the predominant type of PH not always straightforward, 15 and complicating the management of these patients.…”
Section: Types Of Pulmonary Hypertension In Systemic Sclerosismentioning
confidence: 99%
“…Chronic lung diseases including pulmonary fibrosis lead to the elevation of pulmonary artery pressure and right heart failure [6]. CTD-associated PH is known to originate, by different pathogenesis, from PH due to lung disease in which hypoxia induces vascular change [7]. In CTD-associated PH, autoimmune response mediates vascular hypertrophy and fibrosis in pulmonary artery and it advances to a status without hypoxia.…”
Section: Introductionmentioning
confidence: 99%